Lesser Pumpkin Fly, Ethiopian Fruit Fly, Cucurbit Fly, Dacus ciliatus (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr. (EDIS)
The lesser pumpkin fly, Dacus ciliatus (Loew), is one of several fruit flies found in Africa and Asia which could be expected to become serious pests of Florida agricultural crops if introduced into this state. This species has not been intercepted in the United States, but prospects are likely for this to occur because of our heavy international traffic. This document is EENY-258 (originally published as DPI Entomology Circular 81), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.